Time-consistent consumption taxation - Sarolta Laczo; Raffaele Rossi (Queen Mary University of London, School of Economics and Finance, 2018)
We characterise optimal tax policies when the government has access to consumption taxation and cannot credibly commit to future policies. We consider a neoclassical economy where factor income taxation is distortionary within the period, due to endogenous labour and capital utilisation and non-tax-deductibility of depreciation. Contrary to the case where only labour and capital income are taxed, the optimal time-consistent policies with consumption taxation are remarkably similar to their Ramsey counterparts. The welfare gains from commitment are negligible, while they are substantial without consumption taxation. Further, the welfare gains from taxing consumption are much higher without commitment.
Keywords: E62; H21; 330; fiscal policy; Markov-perfect policies; consumption taxation; variable capital utilisation